Teknik Retorika Mahasantri Dalam Meningkatkan Kemampuan Dakwah di Ma’had Al-Jami’ah Uinsu Medan - Khairunnisa Syakirah; Muhammad Husni Ritonga; Tengku Walisyah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
The purpose of this study was to determine the rhetorical techniques used by mahasantri (students) in improving their da'wah (preaching) abilities at Ma'had Al-Jami'ah, UIN Sumatera Utara (UINSU). This research employs a qualitative approach, using data collection techniques such as interviews and direct observations conducted in the field. The study focuses on how rhetorical techniques influence the development of da'wah skills among mahasantri, with particular attention to their speaking abilities. During the research, various rhetorical techniques were identified, including the use of persuasive language, storytelling, metaphors, and repetition, which are commonly employed by mahasantri in their da'wah activities. These techniques are believed to enhance the clarity and effectiveness of the message being delivered, allowing mahasantri to connect more effectively with their audience. The results indicate that the mahasantri at Ma'had Al-Jami'ah have shown significant improvements in their speaking abilities due to the application of these rhetorical strategies. Moreover, these techniques help them in presenting religious teachings in a more engaging and impactful manner. The study also highlights the importance of developing communication skills through rhetorical techniques as a means to enhance the overall quality of da'wah. In conclusion, the research demonstrates that the use of rhetorical techniques plays a crucial role in strengthening the ability of mahasantri in delivering da'wah and improving their public speaking skills. The study recommends further development of such techniques in religious education to foster better communication between the preacher and the community.